2007
DOI: 10.1158/1078-0432.ccr-07-0517
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Paclitaxel Prior to Intratumoral Dendritic Cell Vaccine Modulates Intratumoral Cytokine Network and Lung Cancer Growth

Abstract: Purpose-The main goal of this study was to provide the "proof-of-principle" that low-dose paclitaxel is able to change the tumor microenvironment and improve the outcome of intratumoral dendritic cell vaccine in a murine lung cancer model. Experimental Design-We evaluated the antitumor potential and changes in the intratumoral milieu of a combination of low-dose chemotherapy and dendritic cell vaccine in the Lewis lung carcinoma model in vivo.Results-The low-dose paclitaxel, which induced apoptosis in ~10% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 47 publications
5
95
1
1
Order By: Relevance
“…In this aspect, it was reported that PTX and other chemotherapeutic agents could up-regulate DC functions in vitro. 79 Studies from our group showed that low noncytotoxic concentrations of doxorubicin, methotrexate, mitomycin C and PTX directly up-regulate the ability of DCs to present antigens for Ag-specific T cells in vitro. These drugs significantly up-regulate the expression of CD80, CD86, CD40 and MHC class II molecules on DCs.…”
Section: Immunomodulatory Effects Of Ultra-low Concentrations Of Chemmentioning
confidence: 96%
See 1 more Smart Citation
“…In this aspect, it was reported that PTX and other chemotherapeutic agents could up-regulate DC functions in vitro. 79 Studies from our group showed that low noncytotoxic concentrations of doxorubicin, methotrexate, mitomycin C and PTX directly up-regulate the ability of DCs to present antigens for Ag-specific T cells in vitro. These drugs significantly up-regulate the expression of CD80, CD86, CD40 and MHC class II molecules on DCs.…”
Section: Immunomodulatory Effects Of Ultra-low Concentrations Of Chemmentioning
confidence: 96%
“…67 These observations supported the design of intratumoral administration of DCs after pretreatment of tumor-bearing mice with LDM PTX. 79 Such combination inhibits the s.c. development of murine lung cancer, increasing the infiltration of CD4þ and CD8þ cells. Increased survival was also correlated with release of IFN-c by draining lymph nodes lymphocytes and local production of MCP-1 and IP-10.…”
Section: Immunomodulatory Effects Of Ptx and Combination With Immunotmentioning
confidence: 99%
“…[26][27][28] To create a DC-based cancer vaccine capable of generating LLC-associated antitumor immunity, the DCs were pulsed with whole lysates of LLC cells, as shown in Supplementary (Figures 3f-g). Antitumor effects were determined via caliper measurement and 18 Ffludeoxyglucose ( 18 F-FDG) PET/CT imaging.…”
Section: Anti-tumor Immune Responses Of Rie-aunp-labeled Dcsmentioning
confidence: 99%
“…For example, the antimicrotubule taxanes (paclitaxel and docetaxel) were found to trigger the production of cytokines by macrophages to activate other immune cells, such as DCs (15), NK cells (16), and CTLs, against tumors (16,17). Paclitaxel also reduced the number of regulatory T (Treg) cells and myeloid-derived suppressor cells (MDSCs), and led to the augmentation of the functions of CD4 and CD8 T cells (16,17).…”
Section: Significancementioning
confidence: 99%
“…For example, the antimicrotubule taxanes (paclitaxel and docetaxel) were found to trigger the production of cytokines by macrophages to activate other immune cells, such as DCs (15), NK cells (16), and CTLs, against tumors (16,17). Paclitaxel also reduced the number of regulatory T (Treg) cells and myeloid-derived suppressor cells (MDSCs), and led to the augmentation of the functions of CD4 and CD8 T cells (16,17). In other cases, DNA alkylating agents, such as cyclophosphamide and mafosfamide, in low doses selectively depleted Treg cells (18,19), caused an increase in effector T cells (Teff)/Treg cell ratios via up-regulation of the T helper (Th) 17 pathway (20), and improved the outcome of tumor vaccinations against cancer (21)(22)(23).…”
Section: Significancementioning
confidence: 99%